Structural Performance of High-Strength Reinforced Concrete Beams Built with Synthetic Fibers - Bastami, Roukaya (Université d'Ottawa / University of Ottawa, 2019)
This thesis presents the results of a research program examining the effects of macro-synthetic fibers on the shear and flexural behaviour of high-strength concrete (HSC) beams subjected to static and blast loads. As part of the study, a series of seventeen fiber-reinforced HSC beams are built and tested under either quasi-static four-point bending or simulated blast loads using a shock-tube. The investigated test parameters include the effects of: macro-synthetic fibers, fiber hybridization, combined use of fibers and stirrups and longitudinal steel ratio and type. The results show that under slowly applied loads, the provision of synthetic fibers improves the shear capacity of the beams by allowing for the development of yield stresses in the longitudinal reinforcement, while the combined use of synthetic fibers and stirrups is found to improve flexural ductility and cracking behaviour. The results also show that the provision of synthetic fibers delays shear failure in beams tested under blast pressures, with improved control of blast-induced displacements and increased damage tolerance in beams designed with combined fibers and stirrups. The study also shows that the use of hybrid fibers was capable of effectively replacing transverse reinforcement under both loading types, allowing for ductile flexural failure. Moreover, the use of synthetic fibers was effective in better controlling crushing and spalling in beams designed with Grade 690 MPa high-strength reinforcement. Furthermore, the results demonstrate that synthetic fibers can possibly be used to relax the stringent detailing required by modern blast codes by increasing the transverse reinforcement hoop spacing without compromising performance. As part of the analytical study, the load-deflection responses (resistance functions) of the beams are predicted using sectional (moment-curvature) analysis, as well as more advanced 2D finite element modelling. Dynamic resistance functions developed using both approaches, and incorporating material strain-rate effects, are then used to conduct non-linear single-degree-of-freedom (SDOF) analyses of the blast-tested beams. In general, the results show that both methods resulted in reasonably accurate predictions of the static and dynamic experimental results.
Keywords: Macro-synthetic fibers; Hybrid Fibers; High-strength concrete; Fiber-reinforced concrete; Blast; Shock-tube; Shear; Flexure; Beams; Finite element analysis